The Effect Of Game-Based Learning Methods On The Improvement Of Students' Physical Fitness At Smp Negeri 4 Bantimurung - Fachrul Anam; Syahruddin; Juhanis (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aimed to examine the effect of game-based learning methods on improving the physical fitness of ninth-grade students at SMP Negeri 4 Bantimurung. The background of this study was based on the low level of students' physical fitness, which was influenced by limited effective physical activity and the use of conventional learning methods that tend to be monotonous and less engaging in Physical Education (PJOK) classes. This study employed a quasi-experimental method with a two-group pretest–posttest design. The research sample consisted of 30 male students aged 14–15 years, who were divided into an experimental group and a control group. Physical fitness was measured using the Progressive Aerobic Cardiovascular Endurance Run (PACER) test. The results showed that the experimental group that received game-based learning treatment experienced a significant improvement in physical fitness, with a mean increase of 3.68. Meanwhile, the control group, which received conventional learning, also showed an improvement, but with a lower mean increase of 0.89. Statistical analysis using paired-sample t-tests and independent-sample t-tests indicated a significant difference in physical fitness improvement between the two groups (p < 0.05).